DOES VITAMIN D REDUCE THE MORTALITY RATE OF PLASMODIUM INFECTION? : A SYSTEMATIC REVIEW - Andhira Prilialoka, Dhea (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Malaria is widespread in tropical and subtropical regions, causing more than 300 million acute illnesses and resulting in more than 600,000 deaths annually. Vitamin D (VD) is a fat-soluble vitamin that is synthesized in the skin after exposure to solar ultraviolet B radiation or provided in food. In addition to its traditionally recognized role in the regulation of bone metabolism and calcium-phosphorus homeostasis, VD is increasingly recognized to have prominent regulatory functions in both the innate and adaptive immune systems. The aim: This study aims to show that vitamin D reduce the mortality rate of plasmodium infection or not. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 411 articles, whereas the results of our search on SagePub brought up 49 articles. The results of the search conducted for the last year of 2013 yielded a total 362 articles for PubMed and 36 articles for SagePub. The result from title screening, a total 4 articles for PubMed and 16 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Vitamin D affects the survival rate of individuals infected with Plasmodium. Although mouse models may not accurately reproduce the clinical picture and pathophysiology of malaria in humans, the studies conducted have been instrumental in providing information on how to design appropriate studies in humans.